Pemilihan Pemimpin Non-Muslim di Wilayah Mayoritas Muslim Perspektif Nahdatul Ulama dan Mummadiyah - Muhammad Wildan; Muammar Bakry (Universitas Islam Negeri Alauddin Makassar, 2021)
This article discusses non-Muslim leaders in the region choosing Muslims from the views of Nahdlatul Ulama and Muhammadiyah. The formulation of the problem to be answered in this study is What is the leadership succession procedure in Islam? (2) What is the fiqh view of non-Muslim leadership? (3) What is the view of the Islamic community organizations Nahdlatul Ulama and Muhammadiyah on the law of choosing non-Muslim leaders in Muslim-majority areas?The type of research used by the author is library research which is guided by data processing and is also obtained from various literature related to the title of this article which is sourced from primary data and secondary data. The research approach used is a political approach. The results of this study indicate that the leadership succession procedure in Islam there is no standard and standard procedure set by the Al-Qur'an and Hadith, but the jumhur of ulama agrees that leaders in Islam are chosen in two ways, namely appointed by ahlul halli wal aq in the election committee and appointed by the previous leader. The majority of fiqh scholars view that non-Muslim leadership in Muslim-majority areas is not allowed because their leadership is not valid according to Islamic sharia, unless these non-Muslim leaders lead and control in non-Muslim-majority areas. Meanwhile, in the view of Nahdlatul Ulama and Muhammadiyah regarding the law of choosing non-Muslim leaders, there is already a fatwa stipulation from the two organizations that it is haram to choose non-Muslim leaders but Nahdlatul Ulama provides a little leeway by exempting in an emergency.Keywords: Non-Muslim Leaders, Succession, Nahdlatul Ulama, Muhammadiyah